HPFs filtering solutions for reduced the harmonic current generated by SMPS and ac drive systems - K. Kularbphettong; C. Boonseng (My University, 2020)
This paper proposes a reduced 2nd, 3rd, 5th and 7th harmonic current of all power supply units and ac drives which effects of heating neutral cables and transformer. The commercial or automation building require the operation of many parallel-connected switch mode power supply and ac drive on the same bus and transformer. Such a system significantly increases the high neutral current and power quality problems on the distribution network. The existing system mainly consists of switch mode power supply and a three phase ac drive for compressor loads (common to HVAC applications). A passive power filter (PPF) and a low rating APF (Active Power Filter) at point of common coupling (PCC) are used to power quality enhancement in the distribution system. A PPF is designed to reduce the harmonics and to compensate the reactive power in the distribution system and the APF located at an upstream position near main distribution broads (MDB), it performs the compensation for harmonic current which is produced from all of drive and for remaining harmonics after the PPFs can been operation. The Hybrid Power Filter System (HPFs) is the combination of PPF and APF which mostly use for reducing harmonic currents and improving power quality of the system. Finally, using the HPFs to solve this problem, the results can reduce distortion and neutral current.
Keywords: Harmonic; Power Quality and Harmonics